Method for the Stabilization and Immobilization of Enzymatic Extracts and Its Application to the Decolorization of Textile Dyes - Oyarzun-Medina, M; Oyarzun-Medina, M (SPRINGER, 2014)
Peroxidases from Pleurotus eryngii have been investigated for their ability to degrade recalcitrant, phenolic pollutants. The use of crude enzymatic extracts can reduce the high costs associated with enzyme purification, and enzyme immobilization can enhance enzyme stability and recovery. The present study tests the effectiveness of various conditions for crude enzyme stabilization in polyethylene glycol and glycine solutions, and immobilization on monofunctional and heterofunctional agarose solid supports. Glycine at 0.5 M at 4 °C and pH 4 was most effective stabilization agent for the crude enzymatic extracts, and enzyme immobilization efficiency was greatest for heterofunctional supports. MANA-glyoxyl heterofunctional supports were demonstrated to have the greatest enhancement of decolorization (1.3-fold) and velocity of substrate consumption (fivefold). Therefore, the application of crude enzymatic extracts to industrial processes, such as dye decolorization, represents a cost-effective alternative to purified enzymes. © 2014 Springer Science+Business Media Dordrecht.